Triiodothyronine acts on DAO to regulate pulmonary fibrosis progression by facilitating cell senescence through the p53/p21 signaling pathway - Guo, Xiaoshu; Xu, Kai; Wang, Lan; Ding, Linke; Li, Wenwen; Zhang, Xinsheng; Zhao, Weiming; Wang, Ningdan; Wang, Gaiping; Zhao, Wenyu; Rosas, Ivan; Yu, Guoying (Frontiers in Pharmacology, 2024)
Background: Idiopathic pulmonary fibrosis (IPF) is the result of multiple cycles of epithelial cell injury and fibroblast activation; currently, there is no clear etiology. Increasing evidence suggests that protein metabolism and amino acids play a crucial role in IPF, but the role of D-amino acids is not yet clear. The aim of this study was to identify novel mediators in order to test the hypothesis that D-amino acid oxidase (DAO) plays a significant role in the pathogenesis of IPF. Methods: We analyzed DAO gene expression in patients with IPF and mice with bleomycin (BLM)-induced lung fibrosis. We performed in vitro and in vivo assays to determine the effect of DAO on primary type II alveolar epithelial cells from mice and A549 cells. Results: DAO expression was downregulated in the lungs of IPF patients and BLM-induced fibrotic mice. Treatment with D-serine (D-Ser) or drug inhibition of DAO promoted cell senescence through the p53/p21 pathway. Dao-/- mice showed an intensified fibrotic response, and the anti-fibrotic role of T3 was abolished. Conclusions: We concluded that the DAO-p53/p21 axis might be a key anti-fibrotic pathway regulating the progress of fibrosis and facilitating the therapeutic role of T3.